Efficacy and safety of bevacizumab in elderly patients with metastatic colorectal cancer: results from the Czech population-based registry - Slavicek, Lubomir; Pavlik, Tomas; Tomasek, Jiri; Bortlicek, Zbynek; Buchler, Tomas; Melichar, Bohuslav; Vyzula, Rostislav; Prausova, Jana; Finek, Jindrich; Majek, Ondrej; Dusek, Ladislav (BMC gastroenterology, 2014)
BACKGROUND: Patients aged 65 years and older represent the majority of patients with metastatic colorectal cancer (mCRC). However, this patient population is often underrepresented in clinical trials and probably undertreated in the clinical practice. METHODS: We have analysed the outcomes of 3,187 mCRC patients treated with first-line bevacizumab based on data from the Czech national registry of mCRC patients aiming to compare the treatment efficacy and safety according to the age categories. RESULTS: In total, 2,126 (66.7%), 932 (29.2%), and 129 (4.0%) patients were aged <65 years, 65 to 75 years, and 75+ years, respectively. Median progression-free survival (PFS) was 11.4, 11.3, and 11.8 months for patients aged <65 years, 65 to 75 years, and 75+ years, respectively (p = 0.94). Median overall survival (OS) was 26.9, 27.5, and 25.1 months for patients aged <65 years, 65 to 75 years, and 75+ years, respectively (p = 0.73). Using multivariable Cox model for both PFS and OS, the patient age was not significantly associated with either PFS or OS. No increase in bevacizumab-related toxicity was observed among the elderly mCRC patients with the exception of hypertension, which was observed in 71 (3.3%), 34 (3.6%), and 10 (7.8%) patients aged <65 years, 65 to 75 years, and 75+ years, respectively. CONCLUSIONS: The results of the present study suggest similar outcome in terms of OS and PFS with bevacizumab-containing therapy in elderly mCRC patients fit for chemotherapy combined with targeted therapy compared to younger patients. Thus, chronological age should not be considered to represent a limitation in prescribing bevacizumab-containing therapy in mCRC patients.
Keywords: Registries; deoxycytidin; proporcionální rizikové modely; Capecitabine; Humans; fluoruracil; lidé středního věku; Proportional Hazards Models; capecitabinum; Hypertension; registrace; Leucovorin; Female; Aged; Antineoplastic Agents; protokoly protinádorové kombinované chemoterapie; věkové faktory; senioři; lidé; humanizované monoklonální protilátky; leukovorin; přežití bez známek nemoci; Oxaloacetates; Antibodies, Monoclonal, Humanized; bevacizumab; ženské pohlaví; Kaplanův-Meierův odhad; kolorektální nádory; Male; Middle Aged; Deoxycytidine; hypertenze; Retrospective Studies; Thromboembolism; Antineoplastic Combined Chemotherapy Protocols; Czech Republic; Fluorouracil; protinádorové látky; Bevacizumab; oxalacetáty; Disease-Free Survival; organoplatinové sloučeniny; retrospektivní studie; tromboembolie; Age Factors; Kaplan-Meier Estimate; Česká republika; mužské pohlaví; Organoplatinum Compounds; Colorectal Neoplasms